The Tate Gallery 1974-6 : Illustrated Catalogue of Acquisitions. - Tate Gallery, London (London : Tate Gallery, 1978)
Arp, Jean ; Becher, Bernhard and Hilla ; Bell, Vanessa ; Blake, Peter ; Bomberg, David ; Broodthaers, Marcel ; Brooker, William ; Buckley, Stephen ; Burgin, Victor ; Carline, Hilda ; Carline, Richard ; LeWitt, Sol ; etc.
Contents: British Collection Acquisitions, Modern Collection Acquisitions
Engels
boek